1991
DOI: 10.1073/pnas.88.18.8262
|View full text |Cite
|
Sign up to set email alerts
|

Lateral redistribution of cytochrome b6/f complexes along thylakoid membranes upon state transitions.

Abstract: Although the changes in organization of the lightharvesting antenna upon state transitions are well documented, possible changes in the organization of the photosynthetic electron transfer chain have not been directly investigated. Cytochrome b6/f (cyt b6/f), a major protein complex of this electron-transfer chain, has, however, been implicated in state transitions through its role in LHCIIkinase activation. State transitions are abolished in cyt b6/f mutants of green algae and higher plants due to the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(138 citation statements)
references
References 31 publications
7
130
1
Order By: Relevance
“…Biochemical evidence obtained on thylakoids fractionated either mechanically or with the detergent digitonin suggested that cytb 6 f was distributed fairly evenly between the grana and stromal lamellae (Boardman and Anderson, 1967;Sane et al, 1970;Cox and Andersson, 1981;Anderson, 1982;Dunahay et al, 1984). This even distribution was supported by immunogold labeling of the cytb 6 f complex in intact thylakoids and by freezefracture electron microscopy studies comparing the wild type and a cytb 6 f-less mutant of the green alga Chlamydomonas reinhardtii (Allred and Staehelin, 1985;Olive et al, 1986;Vallon et al, 1991;Hinshaw and Miller, 1993). By contrast, fractionation with the detergents Triton X-100 or n-dodecyl-a-D-maltoside (a-DM) suggested that the grana were devoid of cytb 6 f and that this complex was confined to the stromal lamellae or grana margins (Berthold et al, 1981;Dunahay et al, 1984;Morrissey et al, 1986;van Roon et al, 2000).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Biochemical evidence obtained on thylakoids fractionated either mechanically or with the detergent digitonin suggested that cytb 6 f was distributed fairly evenly between the grana and stromal lamellae (Boardman and Anderson, 1967;Sane et al, 1970;Cox and Andersson, 1981;Anderson, 1982;Dunahay et al, 1984). This even distribution was supported by immunogold labeling of the cytb 6 f complex in intact thylakoids and by freezefracture electron microscopy studies comparing the wild type and a cytb 6 f-less mutant of the green alga Chlamydomonas reinhardtii (Allred and Staehelin, 1985;Olive et al, 1986;Vallon et al, 1991;Hinshaw and Miller, 1993). By contrast, fractionation with the detergents Triton X-100 or n-dodecyl-a-D-maltoside (a-DM) suggested that the grana were devoid of cytb 6 f and that this complex was confined to the stromal lamellae or grana margins (Berthold et al, 1981;Dunahay et al, 1984;Morrissey et al, 1986;van Roon et al, 2000).…”
Section: Introductionmentioning
confidence: 57%
“…It is reasonable to conclude that the granal cytb 6 f complexes we have colocated with PSII facilitate linear electron transport, while the remaining 40 to 50% located in the stromal lamellae facilitate cyclic electron transport as previously suggested (Albertsson, 2001). Indeed, there is evidence that the distribution of cytb 6 f complexes is dynamically responsive to the PQ redox state, with an increase in the proportion found in the stromal lamellae under conditions where the PQ pool is reduced (Vallon et al, 1991). The absence of cytb 6 f complexes from Triton-and a-DM-derived grana membranes may be due to their selective solubilization by Triton and a-DM detergents, which could explain the holes frequently observed in these membranes and their generally ragged appearance (Dunahay et al, 1984;van Roon et al, 2000;Sznee et al, 2011).…”
Section: Cytb 6 F Complexes Are Distributed Throughout the Grana Membmentioning
confidence: 82%
“…This is commensurate with the recent finding that a fraction of the cytochrome complex migrates from grana to stroma lamellae during state I to state II transition. It was also proposed that the redistribution of cytochrome complex may be related to the mechanism of cyclic electron flow activation around photosystem I [7]. The observations that the kinase is localized primarily at the fringe of grana stacks within a region of approximately 40 nm [S].…”
Section: Resultsmentioning
confidence: 99%
“…In State I, the mobile part of LHCII is associated with PSII. Preferential excitation energy flux to PSII reduces the plastoquinone pool and leads to the activation of the LHCII kinase and phosphorylation of LHCII that is laterally displaced from PSII in the grana to PSI in the stroma lamellae of the thylakoid membranes (Vallon et al, 1991;Delosme et al, 1996). Such a State I to State II transition is associated with a significant fluorescence decrease in C. reinhardtii because as much as 80% of LHCII is displaced.…”
Section: Dynamics Of the Photosynthetic Apparatusmentioning
confidence: 99%